Origins of the hydrothermal dolomites in Middle Permian, Sichuan Basin (SW China): Implication for the relationship with the Emeishan Large Igneous Province - Haofu Zheng; Jiajun He; Xiong Duan; Bo Liu; Anna Travé Herrero; Juan Diego Martín-Martín; Enrique Gómez Rivas (PLoS ONE, 2025)
The Middle Permian dolomites in the Sichuan Basin (SCB) of China include several replacive phases and pore-filling saddle dolomite (Rd3 and Sd). This study investigates the origin of the main hydrothermal phases (Rd3 and Sd), which are composed of medium to coarse, non-planar crystals and are heterogeneously distributed, with abundance decreasing sequentially from the southwestern (SW) to the central and northwestern (NW) SCB. A comprehensive petrographic and geochemical analysis reveals a systematic spatial gradient across the basin: fluid inclusion temperatures, salinities, dolomite ordering degrees, and calculated δ¹⁸Ofluid values all increase from the NW to the SW. This trend reflects a transition from a distal, rock-buffered diagenetic system in the NW, dominated by heated Permian seawater with lower temperatures and less evolved fluid chemistry, to a proximal, fluid-buffered system in the SW. The SW system was controlled by the advective influx of high-temperature, high-salinity basinal brines with a strong crustal signature (e.g., highly radiogenic ⁸⁷Sr/⁸⁶Sr ratios and enriched δ¹⁸Ofluid values), which ascended along basement faults. This large-scale hydrothermal system is directly linked to the thermal and tectonic activity of the Emeishan Large Igneous Province (ELIP). Deep-seated basement faults, reactivated during the ELIP event, acted as the primary conduits for hydrothermal fluid migration. This study also shed light on the regional characteristics and formation mechanisms of dolomites influenced by LIPs or abnormal tectonic activities.